Childhood bereavement and adult mortality: A 65-year follow-up of the Stockholm birth cohort. (30th September 2020) - Hiyoshi, A; Berg, L; Grotta, A; Almquist, Y; Rostila, M
Abstract: About 3% of children in Sweden, 4-5% in the UK, and 5% in the US experience the death of a parent during childhood. The event is highly unexpected and stressful and could have long-term social and health consequences across the life course. To alleviate grief, bereaved children may engage in health-damaging behaviours such as smoking, alcohol or drug abuse, violence, delinquency and risky sexual behaviour. Few studies have been able to study health consequences by childhood parental loss and mechanisms explaining associations across the life course. Using the Stockholm Birth Cohort Study (SBC), including all children born in 1953 in the metropolitan Stockholm area, we examined whether childhood bereavement is associated with all-cause mortality until age 63 and whether various pathways (e.g. economic, behavioral and social circumstances) account for the association. 15, 117 individuals were followed between 1953 and 2018 using survey data and national registry data. We used Cox proportional hazard regression and mediation analysis for survival analysis to decompose direct and indirect effects. The death of a parent was associated with 40 to 50% elevated risk of mortality in offspring, and the association was mediated through delinquent behaviour in adolescence and income in adulthood especially for male offspring. Our findings suggest that parental loss has a life long impact on the mortality risk of bereaved children and that interventions targeting delinquency and socio-economic circumstances in bereaved children could be successful in reducing their excess mortality risk. Key messages: Bereavement in childhood has a life-long impact on health. Interventions targeting delinquency and socio-economic circumstances could be successful in reducing the excess mortality risk.